The competitiveness of soybean plants against weeds depending on the timing of sowing and the rate of sowing - Shevnikov, M.; Lotysh, I. (Scientific Progress & Innovations, 2024)
The influence of weeds is one of the factors limiting the achievement of high soybean yields. The aim of this work was to assess the dependence of the development of the weed component in soybean crops depending on terms of sowing and seed sowing rate. Field experiments were conducted on three soybean varieties, Romantika, Ustya and Vorskla, during 2018–2020. According to the results of the research, it was found that the number of weeds per 1 sq.m during the emergence period fluctuated greatly: during early sowing terms within the limits of 287–374, optimal – 197–244, late – 155–185. The calculated coefficients of crop competitiveness and harmfulness of weed groups in crops make it possible to correctly assess the situation regarding the stability of cultivated plants in agrophytocenoses. It is noted that the criterion for the justified use of protective agents should be the competitive relationship between cultivated plants and weeds. Calculations of the coefficients of competitiveness of crops and harmfulness of weeds help to correctly assess the stability of agrophytocenoses. It was found that with an increase in the density of soybean crops, its resistance to weeds increases. In particular, the coefficient of competitiveness at a sowing rate of 0,5–0,6 mln/pcs. of similar seeds per 1 hectare was 1.10–1.16 (row sowing, 15 cm), and at a denser sowing (0,7–0,8 mln/pcs.) it increased to 1.34–1.55 and 1.61–2.00, respectively. The sowing rate turned out to be a more important factor for soybean yield than the sowing method. The optimal conditions were sowing 0,7 mln/pcs. of similar seeds per 1 hectare, which ensured the highest efficiency of area use. It was determined that the soybean yield compared to the minimum sowing rate of 0,5 mln/hectare of similar seeds was higher by: 25 % with the usual row sowing method (2.05 t/he); by 23.2 % with the wide-row sowing method with row spacing of 45 cm (1.91 t/he); by 26.9 % with strip sowing (1.98 t/he). It was proven that increasing the sowing rate to 0,8 mln/pcs. of similar soybean seeds per 1 hectare did not contribute to a significant increase in crop yield. It was found that late intervention in weed control causes crop loss.